Optimizing a Biowaste Treatment Design for Energy and Environmental Efficiency of an Integrated Farming System in Tien Giang Province - Nguyen, Thi Thu Thao; Nguyen, Viet Thang; Le, Thanh Hai (Journal of Technical Education Science, 2022)
Agricultural wastes can be converted into biofuels. To meet the requirements of biofuels, the conditions of their manufacturing process for these products must be considered. The purpose of this research is to optimize experimental designs for converting biomass into energy products like pyrolysis and pelleting process. The products were optimized in terms of their energy performance while lowering CO2 emissions. In Tien Giang province, we experimented with pyrolysis and pelleting biowastes derived from an integrated farming system in acid sulfate soil. The experimental factors influencing the energy content of products were determined using statistical analysis and optimization methods, and the potential CO2 emissions from the products were calculated. The optimization results revealed that the ideal pyrolysis parameters were 120 minutes of combustion time at 400oC and 30% moisture content of orchard pruning residues. The best pellets were obtained by combining biogas sludge and biochar from mango pruning residues. These products will store approximately 900 kilograms of CO2 emissions a year. The optimized processes would benefit the environment and bring profits to the system.